Doença crônica na infância no contexto de vulnerabilidade social: a experiência da família - Baltor, Marja Rany Rigotti (2011)
The chronicle disease has a permanent character and long duration. Life style and the person s environment is scenario worsen). When a child has chronicle condition, the familiar life suffers deep modifications, both by the frequent hospitalizations and by the treatment process. The major cause of physical disabilities in the childhood is cerebral palsy. It is caused by damage or bad formation of the brain. It s defined as a group of permanents disorders that affect the posture s development and movement, affecting major senses, self-care activities, behaviors, communication and intellect. There are others facts associated such as the financial impact once the cost of treatment and materials involved in the care of that child raise up with time and became a source of significant worries to the family. In situation of poverty the chronicle condition has a strong impact on the family, therefore it becomes necessary the reflection and recognize mechanisms to support this clientele. It was used Symbolic Interactionism as a theoretical framework and Content Analysis as method. To data collection it was used semistructure interview to compose the genogram and ecomap, which were tools that helped us characterize the family composition. Six families living in an area of social vulnerability composed the study. The data analysis allowed the conclusion that health professionals are not considered as a support or informational resource. The own family is the main support to cope with chronicity, both emotionally and financially. However, even with family s support, the care is centralized in the mother, and its path is considered as lonely and physically intense. The necessity of one of the family members stop working associated with the high cost of the materials destined to the child has a burly financial impact on the family, consequently is required to reorganize the priorities of investments, and the child health assistance is normally selected as the first one. Even with some financial difficulties, they invest in a private health care insurance to the child, as a result of the delays to access care and failure of the public health care system to resolve the problem in a short term, permanents sequels are brought to those in development and growth process.